Environmental awareness, firm sustainability exposure and green consumption behaviors. (20th September 2020) - Rustam, Adeela; Wang, Ying; Zameer, Hashim
Abstract: This study aims to investigate the potential effects of corporate environmental sustainability reporting on green consumerism. The study employed both primary and secondary data. The primary data collected using a survey method. Whereas, the secondary data on sustainability reporting collected from the company's annual reports and the global reporting initiatives database. Multiple regression techniques employed to assess the data results. The study outcomes indicate that firm's sustainability exposure and environmental responsiveness act as game-changer for green consumption practices, which ultimately be the threshold for changing the rationality and customer's green choices. The results further revealed that environmental awareness significantly moderates the nexus between environmental disclosure and customer's willingness to involve in eco-responsible consumption activities. The study hypotheses have practical significance and extend the theory of planned behavior by locating behavioral and non-behavioral constructs, in shaping eco-friendly consumption. Hence, the study findings propose new insight of relationship into sustainability literature by transforming the firm's environmental exposure in sustaining greener consumption practices to protect the environmental damage by human activities. The present study put forward the policy guidelines that the intervention of firms into environmental activities and persistent sustainability policies helps to stimulate green consumption behavior. Graphical abstract: Image 1 Highlights: Environmental disclosure integrates consumer's eco-consciousness and firm's eco-responsiveness. Behavioral intentions alone do not stimulate pro-environmental consumption. Green consumption choices involve independent factors rather than behavioral intentions. The firm's environmental activities transform customer's green intentions into green behavior. Economic factors sustain eco-responsible behavior, either eco-awareness and exposure is high or low.